ҒАЛАБА ХАБАР ҚУРАЛЛАРЫНДА ӘДЕБИЙ ТИЛДЕН ПАЙДАЛАНЫЎ МАШҚАЛАЛАРЫ - Оразымбетова, З.Қ. (FAN va JAMIYAT, 2018)
The article deals with the specific peculiarities of the literary language and the language of mass media, effectiveness of the newspaper style, methods and issues of using the functional styles of the literary language.